Declining bowel cancer incidence and mortality in germany: an analysis of time trends in the first ten years after the introduction of screening colonoscopy = Rückgang der Inzidenz und Mortalität von Darmkrebs in Deutschland : Analyse zeitlicher Trends in den ersten 10 Jahren nach Einführung der Vorsorgekoloskopie - Brenner, Hermann; Schrotz-King, Petra; Holleczek, Bernd; Hoffmeister, Michael (Deutsches Ärzteblatt, 2016)
Bowel cancer is one of the most frequently diagnosed cancers. Worldwide, every year about 1.4 million people develop bowel cancer and in approximately 700 000 people the disease is fatal (1). In international comparisons, Germany is among the...